Diagnostic and Hematological Study in Sheep Infected With Gastrointestinal Nematode in Mosul City - Dhiyaa A. Moosa; Ali M. Hussien; Hajir M. Hameed; Saad A. Hasan (مجلة الانبار للعلوم البيطرية, 2022)
The aim of this study was to investigate the infection rates as well as the types of Gastrointestinal worms in local sheep admitted to the veterinary teaching hospital at the University of Mosul from the beginning of March 2021 until the end of August 2021, the study also included the effect of Gastrointestinal worms on blood picture in affected animals, 120 faeces and blood samples were collected from native sheep, 12 sheep were clinically normal and negative for gastrointestinal tract parasites and served as control, the results of laboratory examination of faeces samples showed 80 (120) samples were positive for Gastrointestinal worms with a total of infection rate 66.66%, Infection with eggs of Marshallagia spp represented the highest rate of infection amounting to 50 %, followed by infection with eggs of Ostertagia spp at a rate of 17.5 %, while the percentage of infection with eggs of Haemonchus spp. was 15%, Oesophagostomum spp. Nematodirus.spp, Trichostrongylus Spp had the lowest infection rates( 7.5,5.5) % respectively. Blood pictures of infected animals showed a significant decrease (P<0.05) in Red Blood Cell count (RBC), Pack Cell Volume (PCV), and Hemoglobin (Hb), with a significant increase (P<0.05) in Mean Corpuscular Volume (MCV), without significant changes in mean corpuscular haemoglobin concentration (MCHC) values, compared with a control group, while ESR values increased significantly in infected animals compared with control, the Result was showed a significant increased in Total leucocyte count with eosinophilia and lymphocytosis. These results showed the wide spread of Gastrointestinal worms infection in sheep in Mosul city, in addition to its effect on the blood picture.